2014
DOI: 10.1128/aac.02421-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pharmacokinetics and Pharmacodynamics of Liposomal Amikacin for Inhalation in Cystic Fibrosis Patients with Chronic Pseudomonal Infections Using Data from Two Phase 2 Clinical Studies

Abstract: The pharmacokinetic-pharmacodynamic (PK-PD) relationships between serum exposure measures of liposomal amikacin for inhalation (LAI) and the change in pulmonary function test (PFT) measures and number of CFU from baseline were evaluated in cystic fibrosis (CF) patients chronically infected with Pseudomonas aeruginosa. A dose of 70, 140, 280, or 560 mg of LAI or placebo was administered to CF patients once daily for 28 days. PFTs and sputum samples for microbiology were assessed on days 7, 14, 21, 28, 35 (for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…We administered 590 mg of LAI (70 mg/mL), at 1 daily dose (according to a previous pharmacokinetic/pharmacodynamic study [ 12 ]), every day for 3 months and then every other month. Each patient received clarithromycin as well, as a continuous treatment, during the entire evaluation period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We administered 590 mg of LAI (70 mg/mL), at 1 daily dose (according to a previous pharmacokinetic/pharmacodynamic study [ 12 ]), every day for 3 months and then every other month. Each patient received clarithromycin as well, as a continuous treatment, during the entire evaluation period.…”
Section: Methodsmentioning
confidence: 99%
“…Liposomal amikacin for inhalation (LAI) is delivered using an optimized nebulizer, once a day, which allows a rapid delivery of the drug throughout the respiratory tree [ 11 ]. Pharmacological studies on humans focused on the use of such a drug against P aeruginosa infection, but mouse models showed that LAI is also effective against NTM, as much as higher concentrations of free amikacin [ 2 , 12 ]. In addition, LAI may reach high levels in alveolar macrophages, and it is associated with macrophage defects in cytokine signaling or pathogen-killing functions [ 11 ].…”
mentioning
confidence: 99%
“…Similar to initial Pa acquisition and eradication, studies differed widely in the crite-ria used to define chronic Pa infection. This included a wide range of timeframes required for sputum specimen positive for Pa: from 3 months [ 42 ]; six months prior to screening [43][44][45][46][47][48][49] [ 57 ] and finally 24 months prior to screening [ 58 ]. Five other studies did not specify a timeframe.…”
Section: Definition Of Chronic Pa Infectionmentioning
confidence: 99%
“…Five other studies did not specify a timeframe. The majority of studies did not specify the total number or type of samples required apart from the following specific definitions: 3 positive specimens within 2 years prior to screening and 1 within 3 months prior to screening [ 58 ]; 2 positive cultures within 12 months prior to screening (1 within the previous 3 months) or positive at screen- ing [ 49 , 52 , 53 , 55 ]. Pa was confirmed using repeated culture as part of the screening or baseline measurements in most of the studies [ 9 , 43-51 , 54 , 56 , 58 , 59 ].…”
Section: Definition Of Chronic Pa Infectionmentioning
confidence: 99%
“…Vor kurzem wurde zusätzlich das Fluorochinolon Levofloxacin als weitere Substanzklasse von der europäischen Arzneimittelbehörde zugelassen [75]. In naher Zukunft wird die Zulassung des Aminoglykosids Amikacin als Inhalationslösung in liposomaler Formulierung (LAI) für die chronische Infektion durch Pseudomonas aeruginosa bei CF erwartet [66,76]. Weitere Substanzen werden zurzeit für die Anwendung als inhalatives Antibiotikum entwickelt [77].…”
Section: Welche Inhalativen Antibiotika Stehen Für Welcheunclassified